Undang-undang perlindungan pemberi maklumat di Malaysia: Satu analisis - Azlin Namili, Mohd. Ali @ Ramli (2023)
Malaysia has enacted Whistleblower Protection Act 2010 (APPM 2010) in response to the call of the United Nations Convention Against Corruption 2003 even though there have been provisions related to the protection of whistleblowers in other acts that provide a different scale of protection. The overlap between the protections provided by these various acts can open up space for the enforcement agencies to choose the provisions they want without taking into consideration the better protection of whistleblowers. Although APPM 2010 has been enacted for quite a long time, there is only one successful case for in favour of whistleblowers under this act which may indicate that APPM 2010 still need to be improved. This study aims to identify the overlap of legal provisions for protection of whistleblowers between the acts. It also identifies the provisions under APPM 2010 that need to be improved by making a comparison with whistleblowers protection legislation in America and England because APPM 2010 is based on those countries but they have made many improvements to it. In fact, this study also looks at the extent to which this act was applied by the enforcement agencies. This study is a social legal study which uses the analytical and critical approach as well as comparative study. It is suitable for analysing and conceptualising legal issues related to enforcement mechanisms and implications of legal rules and principles. Relevant secondary data were studied and interviews were conducted with enforcement agencies monitored by the Legal Affairs Division in the Prime Minister’s Department to observe the application of APPM 2010. The results of the study show that the protection of whistleblowers under APPM 2010 is generally better compared to the provisions of other acts excepts for a few. However, there are many improvements that need to be made to APPM 2010 in order to increase its effectiveness such as creating a more independent channel for providing information apart from enforcement agencies that under the jurisdictions of the government, the definition of whistleblower should be broadened in scope, it is important to create an organization that monitors the protection given to whistleblowers to ensure the welfare of whistleblowers and also drastic and immediate action should be taken against someone who retaliates against the whistleblower. In conclusion, Malaysia needs an effective act to protect whistleblowers to further encourage the provision of information as it is an important tool to specially to combat corruption. From the perspective of application, all enforcement agencies adopt APPM 2010, however with different procedures according to the perspective agencies.